Culturally Responsive Teaching Approach in Improving Learning Outcomes on the Material of Factors Affecting Reaction Rate - Annisa Putria Dewitasari; Ade Tiyas Widyawati; Dewi Anggraini Sudarto; Murniati Lawah; Neni Anugraheni Nurrahmah; Sri Nurainis Naini; Tjahjo Baskoro Widi; Amaria (Journal of Education Action Reseach, 2025)
The low student learning outcomes in the material of factors that influence reaction rates are caused by the lack of connection between the learning context and students' cultural backgrounds. This study aimed to analyse the effectiveness of a culturally responsive learning approach in improving student learning outcomes in the material of factors that influence reaction rates. The techniques used in this study were descriptive, qualitative, and quantitative, with data collection methods including observation and learning outcome tests in the form of pre-tests and post-tests. The study was conducted in three stages: pre-cycle, cycle 1, and cycle 2. The CRT approach was combined with the Problem-Based Learning (PBL) model in each cycle. The results showed a significant increase in learning completeness, from 33.33% in the pre-cycle to 69.44% in cycle 1 and 89% in cycle 2. The CRT approach effectively linked chemical materials with students' cultural backgrounds and daily experiences, improving student learning outcomes. It was concluded that applying a learning approach responsive to students' cultural backgrounds can significantly improve student learning outcomes by making chemical materials more contextual, relevant, and easy to understand. The implication is that integrating local cultural values in the learning process can create a more contextual and relevant learning experience for students.